THE EFFECT OF ON-STREET PARKING ON U-TURN AREA TOWARDS URBAN ROAD PERFORMANCE (STUDY CASE: AFFANDI STREET, YOGYAKARTA) - Prima J Romadhona; Tsaqif Nur Ikhsan (Institut Teknologi Sepuluh Nopember (ITS), 2021)
Affandi St was on high economic activity area. A consequence was the presence of on-street parking at the turning facility (U-turn) caused a conflict in the form of congestion. This research was intended to determine the performance of the road segment, queue length, delay and proposed alternative solutions for improvement. The research was conducted with the field survey method. The analysis was using VISSIM microsimulation refers to Reverse Planning 06/BM/2005 and the level of performance of road performance refers to the Minister of Transport Regulation number PM 96 of 2015. The result indicated that the average vehicle speed of existing conditions VISSIM analysis was 29,26 km/hour for the North to South and 41,43 km/hour for the South to North, the average queue length was 22,23 meters, the average delay time was 13,66 seconds. Three alternative solutions were implementing prohibited on-street parking at the U-turn area. From the three solutions, the best one was a solution with a decreasing percentage was 27,84% for the queue length and 46,53% for the delay, while the speed increases were 38,54% for North to South and 20,20% for South to North.